The Effect Of Accountability, Integrity, Auditor Expertise, Auditor Professional Skepticism, Due Professional Care, Time Budget Pressure And Audit Fees On Audit Quality - Agit Widiyantari Ginting; Sih Mirmaning Damar Endah (Jurnal Indonesia Sosial Teknologi, 2023)
Research Purposes Aims to determine how much influence accountability, integrity, auditor expertise, auditor professional skepticism, due professional care, time budget pressure, and audit fees have on audit quality. Research Methods All auditors who work at the Public Accounting Firm (KAP) Semarang Central Java are the population of this study. A total of 13 public accounting firms with 64 auditors became the research sample. With the help of SPSS version 26, multiple linear regression analysis was performed on the data. Research Results and Findings, The results of hypothesis testing show that integrity, auditor professional skepticism, due professional care, and time budget pressure do not affect audit quality. Meanwhile, accountability, auditor expertise, and audit fees have a positive effect on audit quality.